Literature Review: Analisis Manajemen Logistik Obat di Instalasi Farmasi Dinas Kesehatan Kabupaten/Kota - Sutejo, Erwin; Setiadi, Adji Prayitno; Wibowo, Yosi Irawati; Gondokesumo, Marisca Evalina (Universitas Malahayati, 2025)
ABSTRACT Drug logistics management is a series of activities related to planning, storing, distributing, and disposing of drugs that are managed optimally to ensure the right amount and type of drugs and medical supplies. This study analyzes drug logistics management at the District/City Health Service Pharmacy Installation. Ten articles were retrieved through Google Scholar to conduct a literature review using drug logistics, pharmaceutical installation, and health service. The search results show that the implementation of logistics management is directly related to several problems, including human resources, facilities and infrastructure, planning, storage, distribution, recording, and reporting of drugs. All health services, especially pharmacy, must meet the requirements of drug logistics management. From the literature review results, if implemented properly, drug logistics management at the district/city health service pharmacy installation can increase the efficiency and productivity of services in health facilities Keywords: Disease Drug Logistics, Pharmacy Installation, Health Service ABSTRAK Manajemen logistik obat adalah rangkaian kegiatan yang berkaitan dengan perencanaan, penyimpanan, pendistribusian, dan penghapusan obat yang dikelola secara optimal untuk memastikan jumlah dan jenis obat dan perbekalan kesehatan yang tepat. Studi ini menganalisis pengelolaan manajemen logistik obat di Instalasi Farmasi Dinas Kesehatan Kabupaten/Kota. Untuk melakukan peninjauan literatur, sepuluh artikel diambil melalui Google Scholar dengan kata kunci logistik obat, instalasi farmasi, dan dinas kesehatan. Hasil penelusuran menunjukkan bahwa penerapan manajemen logistik terkait langsung dengan beberapa masalah, termasuk sumber daya manusia, sarana dan prasarana, perencanaan, penyimpanan, pendistribusian, pencatatan, dan pelaporan obat. Semua layanan kesehatan, terutama kefarmasian, harus memenuhi persyaratan manajemen logistik obat. Dari hasil literatur review dapat diambil kesimpulan yaitu manajemen logistik obat di instalasi farmasi dinas kesehatan kabupaten/kota dapat meningkatkan efisiensi dan produktivitas pelayanan di fasilitas kesehatan jika diterapkan dengan baik. Kata Kunci: Logistik Obat, Instalasi Farmasi, Dinas Kesehatan